Types of Multiple Intelligence Common Among College of Education Students at Dammam University and Their Relation with Specialization, Scholastic Year and Grade Point Average(GPA) - Rasheed, Ra’eda Mohammad (European Scientific Journal, ESJ, 2016)
This study aimed to identify the kinds of multiple intelligence common among the College of Education students at Dammam University. The study sample consisted of (201) students specialized in Mathematics, Physics ,Computer Science, English and Kindergarten and the preparatory year of scientific and literary streams. Mackenzie Inventory for Multiple Intelligence (Mackenzie, 1999) was used, after confirming its validity and reliability. The study results indicated an acceptable ratio of multiple intelligence communality among the students of the College of Education at Jubail/University of Dammam regarding the communality of multiple intelligence among them. The most common kind of intelligence was intrapersonal intelligence, while the least common was musical intelligence. The communality level ratio of mathematical-logical intelligence, visual intelligence, linguistic intelligence, interpersonal intelligence (social) and bodily- kinesthetic intelligence were approximate. There was a significant difference attributed to interaction among students’ multiple intelligence, specialization, scholastic year and Grade Point Average (GPA).